Factors that Affect Continuance Usage Intention of E-Wallet Users in Jakarta - Tommy Setiawan Ruslim; Kenny Alexandra (Graduate Program of Universitas Tarumanagara, 2023)
The growth of technology produces many innovative technologies that make people's lives easier. Competition between technology companies is getting fiercer, they are competing to be the number one in their industry. One of the innovative technologies is the e-wallet. The pandemic and social distancing, make contactless technology grow faster. One of the e-wallets is Sakuku by BCA. When the e-wallet industry is increasing, conversely, active Sakuku users are decreasing. This can occur due to several factors such as confirmation, perceived usefulness, perceived ease of use, and satisfaction. This study examines the effect of confirmation, perceived usefulness, perceived ease of use, and satisfaction on the continuance usage intention of Sakuku users in Jakarta. This study uses PLS-SEM as data analysis technique using data from 232 respondents who have filled out online questionnaires via google form. The results of data analysis show that perceived usefulness and satisfaction can directly affect continuance usage intention. Perceived ease of use cannot affect directly but must go through satisfaction. In addition, confirmation, perceived usefulness, and perceived ease of use can affect satisfaction.